VIRUS LIKE PARTICLE WITH EFFICIENT EPITOPE DISPLAY - SALANTI, Ali; THEANDER, Thor; ØRSKOV AGERBÆK, Mette; THRANE, Susan; MIKKEL JANITZEK, Christoph; AGERTOUG NIELSEN, Morten; BERTELSEN, Adam Frederik Sander (2020)
The invention relates to a virus like particle (VLP) based vaccine. The virus-like particle constitutes a non-naturally occurring, ordered and repetitive antigen array display scaffold which can obtain a strong and long-lasting immune response in a subject. The VLP based vaccine may be used for the prophylaxis and/or treatment of a disease including, but is not limited to, cancer, cardiovascular, infectious, asthma, and/or allergy diseases/disorders.